Cloning and sequencing of gene coding antigen of lung cancer, cyfra 21-1 - Chac, Le Dinh; Huyen, La Thi; Huan, Le Quang (Academia Journal of Biology, 2014)
Cytokeratin 19 (CK19), with a molecular weight of 40 kDa, is the specific cytoskeletal structure of simple epithelia. CK19 has been used as a marker of circulating epithelial cells to diagnose cancer metastasis since it is probably one of the most suitable markers for cancer. One of the fragments of CK19, CYFRA 21-1, has been introduced as a tumor marker for primary lung cancer and proven suitable for the diagnosis of squamous cell carcinoma of the lung. We have amplified the gene encoding for CYFRA 21-1 from the lung cancer samples by RT-PCR technology with the specific primers. The gene sequence has a length of 1001 bp and its homology with the gene sequence CYFRA 21.1 (accession number AB041270) from the GenBank data is 99.82%. This sequence has one point mutation G766C when compared with CYFRA 21-1 gene sequence from the GeneBank.